Genomic Characterization of Sulphite Reducing Bacteria Isolated From the Dairy Production Chain - Doyle, Conor J.; O'Toole, Paul W.; Cotter, Paul D. (Frontiers in Microbiology, 2018)
Anaerobic sporeformers, specifically spoilage and pathogenic members of the genus Clostridium, are a concern for producers of dairy products, and of powdered dairy products in particular. As an alternative to testing for individual species, the traditional, and still current, approach to detecting these sporeformers, including non-spoilage/non-pathogenic species, in dairy products has involved testing for a sulphite reducing phenotype [Sulphite reducing Clostridia (SRCs)] under anaerobic conditions. This phenotype is conserved throughout the Order Clostridia. Unfortunately, however, this phenotype is exhibited by other sulphite reducing bacteria (SRBs) also, potentially leading to potential for false positives. Here, this risk was borne out through the identification of several SRBs from industry samples that were identified as Proteus mirabilis and various Bacillus/Paenibacillus sp. Genome wide comparison of a number of representative SRCs and SRBs was employed to determine phylogenetic relationships, especially among SRCs, and to characterize the genes responsible for the sulphite reducing phenotype. This screen identified two associated operons, i.e., asrABC in SRCs, and cysJI in Bacillus/Paenibacillus spp. and P. mirabilis. This screen identified spp. belonging to sensu stricto, Lachnospiraceae and Cluster XIV of the Clostridia all producing the SRC phenotype. This study highlights the inaccuracy of the industry standard SRC test but highlights the potential to generate an equivalent molecular test designed to detect the genes responsible for this phenotype in clostridia.